The Effect of Synchronous and Asynchronous Enrichment Activities on the Achievement of Arabic Language Subject of Fifth Grade Student in Jordan - Alattar , Reham (Dirasat: Human and Social Sciences, 2023)
The purpose of this study is to uncover the effect of synchronous and asynchronous interactive enrichment activities on fifth-grade students' achievement in the Arabic Language subject in Jordan. The study included 72 students who equally were distributed in two empirical groups. One of the groups included boys while the other group included girls. To achieve the objectives of the study, the researcher has prepared an achievement. The validity and reliability of the test were verified. To answer the two questions of the study, it used arithmetic means, standard deviations, and the One and Two-Way Analysis of Variance (ANCOVA). The results of the study indicated an improvement in students’ achievement in the Arabic Language subject, but the analysis of variance showed that there were no statistically significant differences at the significance level (α = 0.05) between the two study groups in the achievement test due to the synchronous or asynchronous interactive activities or interaction with sex. In light of the results of the study, the researcher figured out several recommendations, such as diversification of implementing interactive enrichment activities synchronously and asynchronously and conducting studies related to synchronous and asynchronous learning.